Women and Islam - Kassam, Zayn. (Santa Barbara, Calif. : Praeger, 2010)
A collection of essays to stimulate discussion and help readers achieve a more sober understanding of the lives of Muslim women around the world.
Law and Iranian women's activism / Louise A. Halper -- Gendered space and shared security: women's activism in peace and conflict resolution in Indonesia / Etin Anwar -- Failures of solidarity, failures of the nation-state: nongovernmental organizations and Moroccan women's activism / Rachel Newcomb -- Beyond personal belief? The role of religious identities among Muslim women respect activists / Narzanin Massoumi -- In search of faithful citizens in postcolonial Malaysia: Islamic ethics, Muslim activism, and feminist politics / Azza Basarudin -- Muslim women's scholarship and the new gender jihad / Roxanne D. Marcotte -- New expressions of religiosity: Al Huda international and the expansion of Islamic education for Pakistani Muslim women / Khanum Shaikh --'Women's spirit' and spiritual matter(s)': gender, activism, and scholarship in an Ethiopian eco-spiritual system / Patricia H. Karimi-Taleghani -- Staging politics: new currents in North African women's dramatic literature / Laura Chakravarty Box -- Indonesian women: activist and Islamist spiritual callings / Nelly Van Doorn-Harder -- The dialogs of a new Orientalist discourse: telling tales of Iranian womanhood / Kahani Beguum -- Religious practice and worldview of Muslim women in western Europe / Kari Vogt -- From ritual to redemption : world view of Shi'a Muslim women in southern California / Bridget Blomfield -- Religion as a spring for activism: Muslim women youth in Canada / Katherine Bullock.
Includes bibliographical references and index.
Keywords: Women in Islam; Feminism -- Religious aspects -- Islam; Muslim women -- Islamic countries -- Social conditions